Etiology and Antimicrobial Susceptibility of Middle Ear Fluid Pathogens in Costa Rican Children With Otitis Media Before and After the Introduction of the 7-Valent Pneumococcal Conjugate Vaccine in the National Immunization Program. Issue 2 (January 2015) - Abdelnour, Arturo; Arguedas, Adriano; Dagan, Ron; Soley, Carolina; Porat, Nurith; Mercedes Castrejon, Maria; Ortega-Barria, Eduardo; Colindres, Romulo; Pirçon, Jean-Yves; DeAntonio, Rodrigo; Van Dyke, Melissa K.; de Almeida Carvalho., Elaine Alvarenga
<x xml:space="preserve">Abstract</x> Abstract Acute otitis media (AOM) microbiology was evaluated in children after 7-valent pneumococcal conjugate vaccine (PCV7) introduction in Costa Rica (private sector, 2004; National Immunization Program, 2009). This was a combined prospective and retrospective study conducted in a routine clinical setting in San José, Costa Rica. In the prospective part of the study, which was conducted post-PCV7 introduction (2010–2012), standard bacteriological procedures were used to evaluate the etiology and serotype distribution of middle ear fluid samples collected by tympanocentesis or otorrhea from children aged 3–59 months diagnosed with AOM. E-tests were used to evaluate antimicrobial susceptibility in culture-positive samples. Retrospective data recorded between 1999 and 2004 were used for comparison of bacterial etiology and serotype distribution before and after PCV7 introduction. Statistical significance was evaluated in bivariate analyses at the P-value < 0.05 level (without multiplicity correction). Post-PCV7 introduction, Haemophilus influenzae was detected in 118/456 and Streptococcus pneumoniae in 87/456 AOM episodes. Most H. influenzae isolates (113/118) were non-typeable. H. influenzae was more (27.4% vs 20.8%) and S. pneumoniae less (17.1% vs 25.5%) frequently observed in vaccinated (≥2 PCV7 doses or ≥1 PCV7 dose at >1 year of age) versus unvaccinated children. S. pneumoniae non-susceptibility rates were 1.1%, 34.5%, 31.7%, and 50.6% for penicillin, erythromycin, azithromycin, and trimethoprim/sulfamethoxazole (TMP-SMX), respectively. H. influenzae non-susceptibility rate was 66.9% for TMP-SMX. Between pre- and post-PCV7 introduction, H. influenzae became more (20.5% vs 25.9%; P-value < 0.001) and S. pneumoniae less (27.7% vs 19.1%; P-value = 0.002) prevalent, and PCV7 serotype proportions decreased among pneumococcal isolates (65.8% vs 43.7%; P-value = 0.0005). Frequently identified pneumococcal serotypes were 19F (34.2%), 3 (9.7%), 6B (9.7%), and 14 (9.7%) pre-PCV7 introduction, and 19F (27.6%), 14 (8.0%), and 35B (8.0%) post-PCV7 introduction. Following PCV7 introduction, a change in the distribution of AOM episodes caused by H. influenzae and pneumococcal serotypes included in PCV7 was observed in Costa Rican children. Pneumococcal vaccines impact should be further evaluated following broader vaccination coverage.